Who Benefits from Transshipment? Exogenous vs. Endogenous Wholesale Prices - Dong, Lingxiu; Rudi, Nils (Management Science, 2004)
This paper studies how transshipments affect manufacturers and retailers, considering both exogenous and endogenous wholesale prices. For a distribution system where a single manufacturer sells to multiple identical-cost retailers, we consider both the manufacturer being a price taker and the manufacturer being a price setter in a single-period setup under multivariate normal demand distribution. In the case of the manufacturer being a price taker, we provide several analytical results regarding the effects of key parameters on order quantities and profits. In the case of the manufacturer being a price setter, we characterize the Stackelberg game that arises, and provide several insights into how the game dynamics are affected by transshipments. Specifically, we find that risk pooling makes retailers’ order quantities less sensitive to the wholesale price set by the manufacturer; hence, in general, the manufacturer benefits from retailers’ transshipments by charging a higher wholesale price, while retailers are often worse off. The paper captures the effect of demand correlation and the effect of the number of retailers throughout, and it illustrates the findings by a numerical example. We also provide an interactive Web page for numerical experiments.